Stripping the self away: security, control, and punishment in the practice of strip searches in Spanish prisons - Güerri Ferrández, Cristina (Body Searches and Imprisonment, 2023)
This chapter analyzes the functions of strip searches in Spanish prisons from a criminological perspective. First, it briefly describes the regulation of body searches as security measures and the standards set to protect prisoners’ fundamental right to personal privacy, especially during strip searches. Secondly, the practice of body searches is examined. Drawing on original data from Catalan prisons, it is shown that strip searches are used extensively, usually in a routinary, non-individualized manner, are overused in high-security units, and lead to few positive results. Moreover, an analysis of NPM Annual Reports demonstrates that certain standards, such as avoiding that the person is completely naked during the strip search, are frequently infringed. The chapter goes on to question whether strip searches truly address specific security risks or serve a different purpose. Lastly, I conclude by arguing that, in Spanish prisons, strip searches are used as a form of general prevention and control, and that the systematic targeting of high-security prisoners has a punitive character.